Sûdân Seyahâtnâmesi : Metin ve İnceleme - Mohemed Ali, Khalid Khater (Fatih Sultan Mehmet Vakıf Üniversitesi, Sosyal Bilimler Enstitüsü, 2016)
Bu çalışmada 20. yüzyılın başlarında Osmanlı seyyahlarından Mehmed Mihri tarafından yazılan Sûdân Seyahâtnâmesi adlı eserin “Sudan” kısmı incelenmiştir. Bu bağlamda eserin Osmanlı harflerinden latin harflerine çevirisi yapılmış, sözdizimi ve kelime hazinesi incelenmiştir. Eserin bu kısmında geçen Arapça ve Farsça kelimeler bir sözlük içinde gösterilmiştir.

In this work, we examined the Travel Book of Sudan “Sûdân Seyahâtnâmesi” by Mehmed Mihri written in the beginning of the 20th century. The objective of our work in this research focus on the part of Sudan. It includes a transcription of this part from Ottoman Turkish letters into Latin characters. It’s also contain an analysis of its syntax and lexical peculiarities with a list of glossary.
FSM Vakıf Üniversitesi, Sosyal Bilimler Enstitüsü
Keywords: Mehmed Mihri; Sûdân Seyahâtnâmesi; Türk Dili; Türkçe sözdizimi; Seyahatnameler; Travel Book of Sudan; Turkish Language; Turkish Syntax; Travelogues